Towards a political economy of adult education and globalization: Theoretical insights for confronting wicked problems in global times - John D. Holst (Adult Education Research Conference, 2021)
Our global times are defined and profoundly shaped by globalization. As adult educators, we need theory to help explain the nature of and paths forward from the devastating social, political, and cultural impacts of globalization. Moreover, when we consider the field beyond academia and include social movement-based adult educators, it is important to understand that not only do we need theory, but some of the best theory we need is developed by social movement-based adult educators. This cross-disciplinary theoretical inquiry presents a political economic framework for understanding adult education and globalization that draws on academic and social movement-based theory.
Keywords: Globalization; political economy; precarity; Marx